Design and synthesis of novel dihydropyridine- and benzylideneimine-based tyrosinase inhibitors - Ahmad, Ifraz; Parveen, Warda; Noor, Shah; Udin, Zahoor; Ali, Amjad; Ali, Ijaz; Ullah, Riaz; Ali, Hamid (Frontiers in Pharmacology, 2024)
Tyrosinase inhibitors are very significant as they inhibit enzyme tyrosinase activity and its inhibition is vital for skin care, anti-cancer and anti-browning of fruits and vegetables. This work presents a novel and economic route for new synthetic tyrosinase inhibitors using Amlodipine (4). The novel conjugates 6 (a-o) were designed, synthesized and characterized by spectroscopic analyses e.g., FTIR, LRMS and HRMS. The purified compound 4 was refluxed with various aldehydes and ketones 5 (a-o) for 5-8 hours in methanol at 60-90 °C. This research was completed in step by step manner that the drug was modified to develop therapeutic properties as tyrosinase inhibitors. The structures of synthesized ligands 6 (a-o) were established based on spectral and analytical data. The synthesized compounds 6 (a-o) were screened against tyrosinase enzyme. The kojic acid was taken as standard. All the prepared compounds 6 (a-o) have good inhibition potential against the enzyme tyrosinase. Compounds 6o, 6b, 6f and 6k depicted excellent anti-tyrosinase activity. Compound 6k with IC 50 value 5.34±0.58 µM is outstanding among all these synthesized compounds 6 (a-o) and even more potent thanis as potent as the standard kojic acid (IC 50 6.04±0.11 µM). The In silico studies of the conjugates 6 (a-o) were evaluated via Patch Dock. The compound 6k has shown the score 8999 and an ACE value -219.66 kcal/mol. The structure activity relationship illustrated that the presence of dihydropyridine nuclei and some activating groups at ortho and para positions of benzylimine moiety is the main factor for good tyrosinase activity. The compound 6k could be used as a lead compound for drug modification as tyrosinase inhibitor for skin care, anti-cancer and antibrowning agent for fruits and vegetables.